Morfometri Tubuh Dan Indeks Organ Ayam Broiler [Gallus gallus gallus (Linnaeus, 1758)] Setelah Pemberian Ampas Kelapa Fermentasi Menggunakan Kapang Mucor irregularis - saragih, hendry; Salsabila, Aileen Arhand; Artik, Arba' Ramdhani; Megantari, Priscilla; Ilmi, Miftahul (Fakultas Biologi Universitas Gadjah Mada, 2025)
Broiler chickens are the most popular livestock commodity due to their high protein content. Improving chicken rearing quality is needed to produce high quality chickens. Feed is one of the determining factors for broiler growth. This research was conducted to study the potential of adding broiler feed with fermented coconut pulp using Mucor irregularis on morphometric development and lymphoid organs (bursa fabricius and lien), pectoralis major muscle growth, and small intestine length. Total 180 male broiler chickens (Gallus gallus gallus) post-hatch (DOC) were separated into 5 groups with 3 replicates and each replicate amounted to 12 chickens. The control group (K) was given basal feed, treatment 1 (P1) and P2 were given non-fermented coconut pulp (1% and 2%), while P3 and P4 were given fermented coconut pulp (1% and 2%), chickens rearing were done until 16 days old (3 days of acclimation). Body morphometry measurements were taken and 3 chickens from each group were dissected to measure muscle organ index, bursa fabricius and lien, and small intestine length. Data were analyzed using One-way ANOVA with Duncan's test (α = 0.05). The highest increase in chicken body morphometry, organ index of bursa fabricius, lien, pectoralis major muscle, and length of small intestine is owned by P4 group chickens. Based on the results of this study, it can be seen that the addition of fermented coconut pulp in feed has a good impact on the growth of chicken body morphometry, increased weight and index of lymphoid organs (bursa fabricius and lien) and pectoralis major muscle, and lengthening of the small intestine.